2008
DOI: 10.1103/physrevlett.100.036805
|View full text |Cite
|
Sign up to set email alerts
|

Resonant Phonon Scattering in Quantum Hall Systems Driven by dc Electric Fields

Abstract: Using dc excitation to spatially tilt Landau levels, we study resonant acoustic phonon scattering in two-dimensional electron systems. We observe that dc electric field strongly modifies phonon resonances, transforming resistance maxima into minima and back into maxima. Further, phonon resonances are enhanced dramatically in the nonlinear dc response and can be detected even at low temperatures. Most of our observations can be explained in terms of dc-induced (de)tuning of the resonant acoustic phonon scatteri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

13
91
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(104 citation statements)
references
References 39 publications
13
91
0
Order By: Relevance
“…6,7 The period of phonon-induced oscillations is tunable by an additional dc electric field. 8,9 Also a new type of QHE was enabled in high mobility 2DEGs, the re-entrant integer quantum Hall effect (RIQHE). 10,11 In the regime of the RIQHE the longitudinal resistance between integer filling factors decreases to zero suggesting fractional filling factors, but the corresponding Hall plateaus are quantized at integer values.…”
mentioning
confidence: 99%
“…6,7 The period of phonon-induced oscillations is tunable by an additional dc electric field. 8,9 Also a new type of QHE was enabled in high mobility 2DEGs, the re-entrant integer quantum Hall effect (RIQHE). 10,11 In the regime of the RIQHE the longitudinal resistance between integer filling factors decreases to zero suggesting fractional filling factors, but the corresponding Hall plateaus are quantized at integer values.…”
mentioning
confidence: 99%
“…Therefore, in the presence of microwaves and strong dc electric field the resistivity is explained by the "displacement" mechanism, i. e. in terms of combined inter-Landau level transitions which are composed of both microwave absorption and impurity scattering. Somewhat similar effect of dc electric field on resonant acoustic phonon scattering [21] was recently observed [8].In this Letter, we study the effect of dc electric field on microwave photoresistivity near cyclotron resonance subharmonics of a high mobility 2DES. Surprisingly, the nonlinear response around the second cyclotron resonance subharmonic, ǫ ac = 1/2, closely mimics the response near cyclotron resonance, ǫ ac = 1, despite a factor of two difference in magnetic fields.…”
mentioning
confidence: 97%
“…Another notable effect is Hall field-induced resistance oscillations (HIRO) emerging under strong dc electric field [4,5]. Recently, it was demonstrated that dc field also induces strong resistance suppression [5,6] and zero-differential resistance states [7,8].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the oscillatory behavior in the nonlinear magnetotransport has attracted much attention: in a 2D system even without irradiation, a relatively weak current can induce drastic suppression and strong oscillations of the differential magnetoresistance, and may result in a state of zero-differential resistance. 22,23,24,25,26 Several theoretical models have been proposed in an attempt to explain this interesting nonlinear phenomenon. 27,28,29,30 Numerical examinations based on the current-control transport scheme were shown in good agreement with the experimental observation for differential magnetoresistivity as a function of the ratio of the current density to the magnetic field in both the magnetic-field sweeping and the current-sweeping configurations covering both separated and overlapping Landau level regimes.…”
mentioning
confidence: 99%